Love and resistance of mothers with intellectual disability from ethnocultural communities in Canada. Issue 3 (1st March 2017) - Pacheco, Laura; McConnell, David
Abstract : Background: Mothers with intellectual disability are thought to be passive, dependent and in need of protection. This study contributes to a nascent body of research that challenges this schema, revealing how women with intellectual disability who are mothers resist oppression. Methods: Narrative research methods underpinned by intersectionality theory were used to explore the lives of eight mothers with intellectual disability from various ethnocultural communities in Canada. A total of 33 in‐depth interviews were conducted with these eight women over a period of 2 years. Results: The lives of the women who took part in this study were marked by violence. The women resisted. Their resistance strategies addressed two kinds of relationships: their relationships with others and their relationship with themselves. Conclusion: The women in this study employed strategies of resistance, sometimes at great personal cost, to provide their children with a better life.